Development of Pre-consolidation Pressure Dependence of Mixed Hardening Multisurface Hyperplasticity Model for Better Prediction of Earthquakes Ground Response Analysis - Apriadi, Dedi; Yunita, Halida; Likitlersuang, Suched; Pipatpongsa, Thirapong (Jurnal Teknik Sipil, 2011)
Abstract. It was known that soil behavior is dependent upon the history of loading and exhibits hardening behavior when deformed plastically. This paper presents a formulation of mixed hardening multisurface hyperplasticity model with stiffness factors of the kinematic hardening of the yield surfaces proportional to the pre-consolidation pressure to represent the history of loading. Formulation is emphasized for describing the cyclic loading behavior of clay soils. The advantages of this approach are that it can reproduce smooth transitions from elastic to plastic behavior and allows the stress-reversal history to be memorized by the internal variable function. The Modified Cam Clay yield function is selected as a key model to simulate the stress-strain response. The incremental stressâstrain response is calculated based on a rate-dependent formulation. Finally, this paper describes the importance of development of the formulated soil model to improve current constitutive models for evaluating the effects of local soil conditions on earthquake ground response analysis. Further results of numerical implementation and simulations and also model verification employing the proposed mathematical model formulation will be reported in a future publication. Abstract. Telah diketahui bahwa perilaku tanah akan tergantung dari sejarah pembebanannya dan juga memperlihatkan perilaku hardening apabila tanah mengalami deformasi secara plastik. Tulisan ini menyajikan sebuah formulasi model tanah mixed hardening multisurface hyperplasticity dengan faktor kekakuan kinematik hardening proporsional terhadap tekanan pra-konsolidasi guna merepresentasikan sejarah pembebanan yang terjadi pada tanah. Formulasi ditekankan untuk mendeskripsikan perilaku pembebanan siklik pada tanah lempung. Kelebihan dari pendekatan model hyperplasticity ini adalah dapat menghasilkan transisi dari perilaku elastik ke plastik secara smooth serta mampu âmengingatâ sejarah perubahan tegangan yang terjadi pada tanah dengan menggunakan fungsi variabel internal. Fungsi leleh Modified Cam Clay dipilih sebagai model utama untuk mensimulasikan respons tegangan-regangan. Selanjutnya, respons tegangan-regangan dihitung berdasarkan sebuah formulasi rate-dependent. Terakhir, tulisan ini mendeskripsikan pentingnya pengembangan model ini guna memperbaiki analisis respons tanah akibat gempa. Hasil-hasil lebih lanjut berupa implementasi dan simulasi numerik serta juga verifikasi model yang diusulkan akan disajikan dalam publikasi berikutnya.